Da'wah Through Youtube in The Perspective of Millennial Society - Faridah Faridah; Dian Damayanti; Suriati Suriati (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2023)
Many studies have been conducted on da'wah through YouTube, but the researchers in this study specifically analyzed the use of YouTube for preaching from the perspective of millennial society. This study is a type of descriptive research with a qualitative approach, data obtained through interviews and documentation of several millennial people who are considered representative in providing information related to research needs. The research findings show that people like to watch da'wah through YouTube and da'wah is delivered effectively, the advantages of YouTube in da'wah are in terms of audio-visual presentation of da'wah, flexible time considerations, and completeness of da'wah material delivered compared to da'wah through video on social media. Apart from the joy of being mad'u in participating in da'wah activities via YouTube, they also conveyed that there was a change in mindset, attitude and behavior after listening to the da'wah messages conveyed. This illustrates that the community has felt the benefits of using YouTube as a propaganda medium, such as in the preaching of Ustadz Adi Hidayat, K.H. Abdullah Gymnasitiar, Ustadz Abdul Shomad, Ustadzah Oki Setiana Dewi, Ustadzah Syifa Nurfadhillah who have quite a lot of followers and likes that there are up to thousands and positive comments in each of his studies.